Qaani Shirazi and the school of return in the Qajar Era - Rasheed, Jassim Majeed; Abbas, Anwar (Al-Adab Journal, 2023)
In this research, the researcher dealt with a general and brief study on a group of poets, the most prominent of whom is the poet Qaani Shirazi, who is considered one of the most prominent poets of the Qajar era, who worked hard with a group of poets in that period to revive the ancient Persian literary heritage and formulate it in a new style in a way that revived the language and poetic expressions of Persian Modern, the aim of this research is to know the contemporary poets of that period who took it upon themselves to revive the ancient heritage and also to know the factors that helped bring about a literary constitutional revolution, and what are the prominent types of poetry during that period.